2004
DOI: 10.1111/j.1399-302x.2004.00167.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity of moxifloxacin compared to other antimicrobials against streptococci isolated from iatrogenic oral bacteremia in Spain

Abstract: Most of the streptococci isolated from the bloodstream after dental extractions were susceptible in vitro to penicillin, ampicillin, and amoxicillin. The high percentage of streptococci resistant to erythromycin and clindamycin could restrict their usefulness as prophylactic drugs. All the isolates showed a low MIC of moxifloxacin in vitro, making it a promising antimicrobial alternative for the prevention of streptococcal focal infections associated with certain dental manipulations, when the administration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
18
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 38 publications
(41 reference statements)
1
18
0
2
Order By: Relevance
“…This fluoroquinolone shows good in vitro activity against odontogenic pathogens (23,27,43). Recently, we have found that all the streptococci isolated from a series of patients with iatrogenic bacteremia of oral origin showed a low MIC to MXF (47). Furthermore, we have demonstrated its efficacy in vivo for the treatment of submucous layer dental abscesses, confirming its penetration into tissue in the oral cavity (24).…”
mentioning
confidence: 75%
See 3 more Smart Citations
“…This fluoroquinolone shows good in vitro activity against odontogenic pathogens (23,27,43). Recently, we have found that all the streptococci isolated from a series of patients with iatrogenic bacteremia of oral origin showed a low MIC to MXF (47). Furthermore, we have demonstrated its efficacy in vivo for the treatment of submucous layer dental abscesses, confirming its penetration into tissue in the oral cavity (24).…”
mentioning
confidence: 75%
“…MXF has shown good in vitro activity against both oral streptococci (macrolide-sensitive or -resistant) and anaerobic pathogens (23,27,43,47). Recently, we have found in a series of BDE that all the streptococci isolated showed a low MIC to MXF (47).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…These facts are visible in the species of the viridans group of the genus Streptococcus, where the high resistance to macrolides (erythromycin, clarithromycin) 49 is frequently associated with high resistance to tetracyclines 50 and to clindamycin and azalides (azithromycin). 52 Considering that consumption of antibiotics in dentistry assumes 10% of the total consumption of antibiotics in the community, as mentioned above, it is possible to suspect a not unappreciable degree of responsibility in the selection of resistances due to antimicrobial treatments in dentistry. A high prevalence of oral iatrogenic bacteraemia has been described in our country caused by Streptococci resistant to erythromycin (40.8%) and clindamycin (21%), the majority of the isolates being sensitive to aminopenicillins.…”
Section: Antibiotics and Normal Floramentioning
confidence: 99%